Social Dynamics of Cultural Anthropological Transformations - Soghomonyan, Gagik (Journal of Sociology: Bulletin of Yerevan University, 2016)
In parallel with the civilizational development of the society, the true origins of the social construction gradually enfeeble. The deformation of the social ties and relations threaten to turn into a "social entropy", the social converts into a blank sign, devoid of any objective content. The erosion of the sustainable patterns in groups that represent the social identification, "a new atomization" and its reverse side - "massivization" - is the modern manifestation of the "demise of the social ', its appeal to the" simulacrum ". Does "social death" mean sociocultural retribution for civilization progress? As a result of the comparative-typological analysis of traditional, industrial and postindustrial societies, the author concludes that in the cultural and anthropological sense those countries progress most apart from technical and technological realities of the postmodern society who skillfully combine panhuman socio-cultural universals, traditional and modern values.
Keywords: sociocultural universals, traditional society, tradition, industrial society, alienation, postindustrial society